Negligence and utility. (2nd January 2017) - Beever, Allan
ABSTRACT: This article examines the claim that assessment of the standard of care in the law of negligence utilises and must utilise considerations of utility. It argues that this position is mistaken. It also maintains that cases frequently thought to support this view do not do so. The article also examines the justice of appeals to utility in the relevant cases and examines the appropriate way to deal with emergency situations.